The effect of curing agent on the dynamic tensile failure of an epoxy subjected to plate impact. (March 2018) - Pepper, Jonathan E.; Huneault, Justin; Rahmat, Meysam; Ashrafi, Behnam; Petel, Oren E.
Highlights: Tensile/spall strengths and fracture toughness of two thermosetting polymers were characterized under quasi-static and dynamic loading conditions. Choice of curing agent was shown to have a significant effect of the spall strength and fracture toughness of the epoxy resin, but no appreciable effect on shock response. Spall strength in one epoxy system is shown to be more strongly dependent on the incident shock pressure of loading than the strain rate of unloading. Abstract: Dynamic tensile failure of epoxy resin cured with two different curing agents was studied in terms of spall strength, fracture toughness, and shock behaviour. Plate impact experiments were conducted to examine how the epoxy responds to one-dimensional, high-strain rate loading. Velocity measurements of the back surface of the targets were taken during impact with a photonic-Doppler velocimeter (PDV). The velocity profiles that resulted were analyzed to gain insight on the material interface/stress wave interactions that manifested within the samples. Spall strength measurements ranged from 404 to 585 MPa in EPON 828 cured with EPIKURE 3223, and from 339 to 462 MPa in EPON 828 cured with EPIKURE 3233. Evidence for the existence of a quantifiable relationship between the curing agent used to cure the resin and the dynamic tensile strength of the resulting epoxy is provided. The discrepancies in the measured spall strengths between the two epoxy systems were attributed to a difference in the electrostatic forces between adjacent polymer chains within the crosslinked epoxy network. Strength measurements in both epoxies demonstrated significant strain-rate dependency. Spall strength measurements presented in this study were noticeably higher than those listed in the literature for similar thermosetting polymers, likely the result of the choice of curing agent. Finally, shock and particle velocity measurements were shown to be consistent with previously published results, within experimental uncertainty.